A new hybrid topology optimization method based on I-PR-PSO and ESO. Application to continuum structural mechanics. (February 2019) - Di Cesare, N.; Domaszewski, M.
Highlights: Binary Hybrid PSO algorithm, based on I-PR-PSO and ESO. Application on classical structural mechanics problems. Multi-objective topology optimization. Abstract: The Inverse-PageRank-PSO (I-PR-PSO) algorithm, an optimizer based both on the Particle Swarm Optimization (PSO) algorithm and the PageRank algorithm - used by the well known search engine Google - is applied to continuum structural topology optimization. To deal with the classical continuum mechanics problems of the literature, such as checkerboards in the resulted topologies, the algorithm is interfaced with the Evolutionary Structural Optimization (ESO) algorithm. Several well-studied examples from structural topology optimization problems of minimum weight and minimum compliance are used to demonstrate the efficiency of the newly developed algorithm. The results show the possibility to treat two-objectives problems, even if the two objectives are apparently conflicting, finally finding a compromize that minimizes both the volume and the compliance of the structure.